Impact of Video Games on Players’ Decision-Making Power: A Study of Rawalpindi, Pakistan (Journal of Social Sciences Review, 2025)
In the modern era where video games emerge in the modern technologies, the problem is that many people think that video games have only negative impact on players but the fact is that video gaming has increased the cognitive abilities of the players. The aim of the study is to prove whether video games can really enhance the cognitive abilities or decision-making power of the players. This study is based on quantitative research (survey) designed to examine the impact of video games on player’s decision-making power. For this study selected youngsters from the general public age (16-30). The result of this study proves that video gaming has increased the cognitive abilities of the payers in cognitive abilities including multitasking skills problem-solving abilities, critical thinking abilities, collaborative abilities, fast decision speed, etc. Video games are a big source for the betterment of our cognitive functions. In this era, we see many kinds of entertainment, but video gaming not only provides entertainment video games They enhance multitasking skills, brain functions, problem-solving abilities, critical thinking abilities, collaborative abilities, and goal orientation.
Keywords: Video Games; Decision Making Power; Learning